2022
DOI: 10.1007/s10895-021-02863-5
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide-Functionalized Carbon Quantum Dot as New Sensing Platform for Portable Quantification of Vitamin B12 in Fluorescence, UV–Vis and Smartphone Triple Mode

Abstract: Development of an e cient, portable and simple nanosensor-based systems with reliable analytical performance for on-site monitoring of vitamin B12 (VB12) are still major problems and a challenging work for quality control of manufacturers. Herein, a new uorescence, UV-Vis and smartphone triple mode nanosensors were designed for the simultaneous detection of VB12 with high sensitivity and accuracy. A novel nanosensor was synthesized through nicotinamide-functionalizing on carbon quantum dot (NA-CQDs) by an one-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Another benefit is that it is portable, rapid, and easy to grasp quantitative data that can be read even by unskilled workers, which is extremely useful in regions with limited resources. So far, there have been very few published research on smartphone-integrated point-of-care nanosensors for on-site monitoring of vitamin B 12 in pharmaceutical, food, and beverage additives. …”
Section: Introductionmentioning
confidence: 99%
“…Another benefit is that it is portable, rapid, and easy to grasp quantitative data that can be read even by unskilled workers, which is extremely useful in regions with limited resources. So far, there have been very few published research on smartphone-integrated point-of-care nanosensors for on-site monitoring of vitamin B 12 in pharmaceutical, food, and beverage additives. …”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that the Pi camera, used in conjunction with the microcontroller can be used to image uorescent DNA in agarose gel electrophoresis [23]. This offers the advantage of dedicated operation, as opposed to the use of smartphones, which are more suited for in-situ inspection endeavors [24]. While lasers have been widely used for excitation light delivery, there are alternative light sources that can potentially be more cost effective for use.…”
Section: Introductionmentioning
confidence: 99%